2021
DOI: 10.1096/fj.202001616rr
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bone morphogenetic protein 2 and thrombopoietin treatment on angiogenic properties of endothelial cells derived from the lung and bone marrow of young and aged, male and female mice

Abstract: With an aging world population, there is an increased risk of fracture and impaired healing. One contributing factor may be aging‐associated decreases in vascular function; thus, enhancing angiogenesis could improve fracture healing. Both bone morphogenetic protein 2 (BMP‐2) and thrombopoietin (TPO) have pro‐angiogenic effects. The aim of this study was to investigate the effects of treatment with BMP‐2 or TPO on the in vitro angiogenic and proliferative potential of endothelial cells (ECs) isolated from lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In HUVECs, androgen treatment augments proliferation and migration in male but not female cell lines and this effect is mediated by the androgen receptor, 27 which could explain sex‐based differences in cardiovascular disease with aging. In murine lungs, there are age‐ and sex‐based differences in endothelial cell function, angiogenesis, and gene transcription regulating these pathways, 28 which may also influence human cellular phenotypes. Finally, we noticed substantial variation in behavior and function across cell lines supporting the concept that additional confounders (comorbid illness, BMI, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In HUVECs, androgen treatment augments proliferation and migration in male but not female cell lines and this effect is mediated by the androgen receptor, 27 which could explain sex‐based differences in cardiovascular disease with aging. In murine lungs, there are age‐ and sex‐based differences in endothelial cell function, angiogenesis, and gene transcription regulating these pathways, 28 which may also influence human cellular phenotypes. Finally, we noticed substantial variation in behavior and function across cell lines supporting the concept that additional confounders (comorbid illness, BMI, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…One study found that BMP-2 treatment decreases the migration of endothelial cells in both young and old mice, while endothelial cells from old mice showed better migration than those from young mice (Dadwal et al, 2021).…”
Section: The Bmp Family and Cardiac Agingmentioning
confidence: 99%
“…Compared to LECs, BMECs exhibited significantly more angiogenic mRNA expression differences following treatment with SRT1720. We speculate that this may occur as LECs are isolated as a homogenous CD31+ population whereas BMECs are isolated as a heterogeneous population [ 45 , 46 , 47 , 48 , 49 ] that is comprised of mature and immature EC cells, stalk and tip cells, and perhaps EC-like cells that assist in EC function [ 11 ]. Exploring and comparing the gene profiles between these subpopulations of ECs remains to be investigated but is important to better understand how drugs would impact multiple cell types.…”
Section: Discussionmentioning
confidence: 99%
“…BMECs remained in this culture for seven days before being used for experiments. We have previously characterized BMECs isolated from this procedure by a number of criteria, including the examination of Tie2 expression (as evidenced in BMECs isolated from mice in which tdTomato is expressed under the control of the Tie2 promoter following activation with tamoxifen), CD31 immunocytochemical staining, and flow cytometric analysis (CD45- Ter119- CD31+ CD105+ cells) [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%